Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Write an equation to find the nth term. Then find ₐ₂₄
-1, -4, -7, -10,...


Sagot :

The equation to find the nth term is:

an = a+(n-1)d

Where a is the first term in the sequence, which is -1 and d is the difference, which in this sequence the next term is found by subtracting 3 from the previous term, so d = -3 and n is the term you want to find.

The equation becomes:

an = -1 +(n-1)(-3)

a24 = -1 + (24-1)(-3) = -1 + (23(-3)) = -1-69 = -70